Age‐related decrease in responsiveness of CD271‐positive skin stem cells to growth factors. Issue 8 (13th June 2022) - Akamatsu, Hirohiko; Yamada, Takaaki; Sanada, Ayumi; Ishii, Yoshie; Iwata, Yohei; Arima, Masaru; Hasegawa, Seiji; Sugiura, Kazumitsu
Abstract: Previous studies have demonstrated that the numbers of interfollicular epidermal stem cells (IFE‐SCs) and dermal stem cells (DSCs) decrease with age and that this decrease is attributed to the age‐related deterioration of skin homeostatic functions and the delay in wound healing. Meanwhile, functional decline in the stem cells is also considered to be responsible for the deteriorated skin homeostatic functions and the delayed wound healing associated with ageing. In the present study, we focused on epidermal growth factor/epidermal growth factor receptor (EGF/EGFR) signalling and fibroblast growth factor‐2/fibroblast growth factor receptor (FGF2/FGFR) signalling to analyse the age‐related changes. Immunohistological analysis revealed that the expressions of EGFR and FGFR1 declined in IFE‐SCs and DSCs with age, respectively. Additionally, IFE‐SCs and DSCs isolated from the skin samples of elderly subjects exhibited lowered responsiveness to EGF and FGF2, respectively. These results suggest that the lowered responsiveness of the skin stem cells to growth factors may be a factor involved in the age‐related deterioration of skin regenerative functions during wound healing and skin homeostatic functions. We hope that homeostatic and wound healing functions in the skin could be maintained if the decreased expressions of EGFR and FGFR1 in IFE‐SCs and DSCs, respectively, can be suppressed.